Dynamic multi-actor engagement in networks: the case of United Breaks Guitars. Issue 4 (10th July 2017) - Li, Loic Pengtao; Juric, Biljana; Brodie, Roderick J.
Abstract : Purpose: The purpose of this paper is to explore the dynamic process of multi-actor engagement by examining how it evolves and spreads in actor networks. The authors challenge the dyadic perspective adopted by previous research. Design/methodology/approach: An abductive theorizing approach uses a longitudinal case study to develop a theoretical framework of the iterative process of multi-actor engagement. The authors draw on the contemporary literature on engagement, service-dominant logic and value propositions. Findings: The research shows that engagement conditions, via actors' appraisals, lead to engagement properties and result in engagement outcomes as the new conditions for the next iteration. Changes within this multi-actor engagement process lead the network to evolve over time. Research limitations/implications: The authors highlight the importance of adopting a dynamic multi-actor perspective of engagement and provide foundations for further research. The use of longitudinal methods that focus on the groups of actors in the evolving network is a key consideration. Practical implications: There is the need to understand and measure the dynamic process of engagement among different groups of actors within networks in the service context. Originality/value: This is the first empirical study to explore the dynamics of engagement among multiple actors in the network. This leads to the expansion of Storbacka et al. 's (2016) conceptual work by identifying the iterative nature of the multi-actor engagement process, and new components in the process (i.e. actors' connections, value propositions and engagement outcomes), as well as clarifying existing ones (e.g. engagement properties and actors' appraisals).